Existence of Multiple Solutions for a Class of n-Dimensional Discrete Boundary Value Problems - Weiming Tan; Zhan Zhou (International Journal of Mathematics and Mathematical Sciences)
By using critical point theory, we obtain some new results on the existence of multiple solutions for a class of n-dimensional discrete boundary value problems. Results obtained extend or improve existing ones.